Free and self-trapped exciton emission in perovskite CsPbBr3 microcrystals. Issue 2 (5th January 2022) - Pan, Fang; Li, Jinrui; Ma, Xiaoman; Nie, Yang; Liu, Beichen; Ye, Honggang
Abstract : A broad STE emission band together with a FE emission was found at low temperature in a CsPbBr3 microcrystal sample prepared by CVD method. Abstract : The all-inorganic perovskite CsPbBr3 has been capturing extensive attention due to its high quantum yield in luminescence devices and relatively high stability. Its luminescence is dominated by free exciton (FE) recombination but additional emission peaks were also commonly observed. In this work, a CsPbBr3 microcrystal sample in the orthorhombic phase was prepared by the chemical vapor deposition method. In addition to the FE peak, a broad emission peak was found in this sample and it was attributed to self-trapped excitons (STEs) based on its photophysical properties. The STE emission can only be observed below 70 K. The derived Huang–Rhys factor is ∼12 and the corresponding phonon energy is 15.3 meV. Its lifetime is 123 ns at 10 K, much longer than that of FE emission. The STE emission is thought to be an intrinsic property of CsPbBr3 .